Self-Disclosure and Management of Feminine Male Personas on The Tiktok Platform - Angel Lolita, Florensia; Isnaini, Muhammad (Asian Journal of Social and Humanities, 2023)
Social media platforms are growing every time. The development of social media already has various kinds, such as Facebook, Twitter, Youtube, and others. One of the new social media that is currently very popular is Tiktok. As one of the popular social media, Tiktok is a platform for users to be able to carry out the self-disclosure process, especially male users who tend to be feminine. Self-Disclosure as a Disclosure Process: The process of self-disclosure on TikTok is an act in which male individuals express their feminine side through the videos and content they share. This reflects their openness to identity and self-expression which may differ from the gender stereotypes generally expected of men. There are 2 (two) processes that occur during actual self-disclosure on the Tiktok platform, namely on the front stage and back stage and the management of feminine male personas on TikTok involves an understanding of how these individuals build, maintain and manage their image and identity in those platforms. They use elements such as visual effects, background music, and editing to amplify the message they want to convey and create an impact on their audience. TikTok as a platform provides a "stage" for feminine male individuals to perform and interact with followers and other users. They can upload videos with the style and content they choose, take advantage of TikTok's creative features, and manipulate visual and audio settings to create engaging experiences. This study uses identity theory in the process of self-disclosure, and focuses on male research sources. feminist man. This research uses qualitative methods, constructivist paradigms, sociocultural traditions, and digital phenomena approaches